Design Dan Analisis Solar Battery Charger Berbasis Push-Pull Converter - Hizrian Alnubli; Budhi Anto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This research presents a design of push-pull converter used on battery charging system that is the source of her energy comes from solar pv. Solar pv was used in this research had a 150 watt maximum power with an open circuit voltage of 21.67 volts. The battery is a type of sealed lead acid (SLA) which has a capacity of 24 Ah with a nominal voltage of 12 volts. Solar pv battery fill through chargers controller is a DC-DC converter. DC-DC converter circuit type of push-pull is used to ensure the process of charging the battery so that it takes place on a secure condition even though the solar pv output voltage fluctuates with how to limit the voltage on the battery is charging of 14.1 volt. The system was designed using of Matlab-Simulink software. The results of the simulation shows the automatic setting of duty cycle which is conducted by electronic switches that triggered by the input signal as a part of PI controller. Therefore, a series of push-pull converter able to maintain the output voltage at value of 14,1 volt.Keywords : Push-Pull Converter, Sealed Lead Acid Battery, Chargers Controller, Matlab-Simulink.